An Innovative and Atom-Efficient Synthesis of Bioactive 2-Aroylfuran Derivatives Using Macroporous Polymer-Supported Cyanide - Mouradzadegun, Arash; Abadast, Fatemeh (Synlett, 2014)
A novel and safe approach was developed for the synthesis of bioactive 2-aroyl-3,5-diarylfurans in excellent yields by using a cyanide-impregnated anion-exchange resin as a versatile reagent. The possibility of reusing the polymer-supported reagent makes the process environmentally friendly and economically advantageous.
Keywords: furans; green chemistry; ring contraction; heterocycles; nucleophilic additions